2001
DOI: 10.1016/s0753-3322(01)00052-x
|View full text |Cite
|
Sign up to set email alerts
|

Occult metastasis

Abstract: The most important factor affecting the outcome of patients with invasive cancers is whether the tumor has spread, either regionally (to regional lymph nodes) or systemically. However, a proportion of patients with no evidence of systemic dissemination will develop recurrent disease after primary 'curative' therapy. Clearly, these patients had occult systemic spread of disease that was undetectable by methods routinely employed (careful pathological, clinical, biochemical and radiological evaluation). In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Also, the distance from the tumor, which follows through the epicolic, paracolic, intermediate and principal lymph nodes, respectively, although different lymphatic pathways may exist suggesting the presence of important variables, including tumor invasion of lymphatic channels, changes in the lymphatic drainage pattern, or direct pressure of tumor bulk leading to drainage by alternative lymphatic channels effecting the transport of a single tumor cell via lymphatics (2). Our previous study detected non-continuous nodal metastasis toward the drainage of the lymphatic tract, which was hypothesized to be skip metastasis of colorectal cancer and the frequency of skip metastasis is ~6.5-10.5% (3,4). In the present case study, skip metastasis was confirmed even with the carcinoid, which is typically very slow growing and exhibits a low grade malignant potential.…”
Section: Discussionsupporting
confidence: 65%
“…Also, the distance from the tumor, which follows through the epicolic, paracolic, intermediate and principal lymph nodes, respectively, although different lymphatic pathways may exist suggesting the presence of important variables, including tumor invasion of lymphatic channels, changes in the lymphatic drainage pattern, or direct pressure of tumor bulk leading to drainage by alternative lymphatic channels effecting the transport of a single tumor cell via lymphatics (2). Our previous study detected non-continuous nodal metastasis toward the drainage of the lymphatic tract, which was hypothesized to be skip metastasis of colorectal cancer and the frequency of skip metastasis is ~6.5-10.5% (3,4). In the present case study, skip metastasis was confirmed even with the carcinoid, which is typically very slow growing and exhibits a low grade malignant potential.…”
Section: Discussionsupporting
confidence: 65%
“…This is often called lymph node micro metastasis. 6 To improve the detection of micrometastasis cancer or tumor-related precursor lesions remaining in histologically negative lymph node, molecular lymph node analysis was proposed and now it has been used to observe and predict local recurrence of cervical squamous cell carcinomas. In previous studies, the correlation between the prognosis and the expression of CK19 in histologically negative lymph node of cervical squamous cell carcinoma had been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The only 4 variables that remained statistically significant as independent predictors of the recurrence in the multivariate analysis were CK19 and SCCAg status in sentinel lymph node, FIGO staging, and cervical stroma infiltration depth. The odds ratio (95% confidence interval, P) of the CK19 status, SCCAg status, FIGO staging, and cervical stroma infiltration depth were 6 …”
Section: Multivariate Analysis Of Recurrencementioning
confidence: 99%
“…The most significant limitation of immunohistochemistry is that it cannot provide accurate levels of tumor cell load within the blood. Flow cytometry alone cannot morphologically characterize the epithelial cells within a given blood sample, and requires further confirmation by immunohistochemistry [15, 26, 30]. This takes more time and results in higher reagent costs.…”
Section: Discussionmentioning
confidence: 99%